Discovery of Retinoic Acid-Related Orphan Receptor gamma t Inverse Agonists via Docking and Negative Image-Based Screening - Sanna Rauhamäki; Pekka A. Postila; Sakari Lätti; Sanna Niinivehmas; Elina Multamäki; Klaus R. Liedl; Olli T. Pentikäinen (American Chemical Society, 2025)
Retinoic acid-related orphan receptor gamma t (ROR gamma t) has a vital role in the differentiation of T-helper 17 (TH17) cells. Potent and specific ROR gamma t inverse agonists are sought for treating TH17-related diseases such as psoriasis, rheumatoid arthritis, and type 1 diabetes. Here, the aim was to discover novel ROR gamma t ligands using both standard molecular docking and negative image-based screening. Interestingly, both of these in silico techniques put forward mostly the same compounds for experimental testing. In total, 11 of the 34 molecules purchased for testing were verified as ROR gamma t inverse agonists, thus making the effective hit rate 32%. The pIC(50) values for the compounds varied from 4.9 (11 mu M) to 6.2 (590 nM). Importantly, the fact that the verified hits represent four different cores highlights the structural diversity of the ROR gamma t inverse agonism and the ability of the applied screening methodologies to facilitate much-desired scaffold hopping for drug design.